Mining the genome of Bacillus velezensis FS26 for probiotic markers and secondary metabolites with antimicrobial properties against aquaculture pathogens - Sam-on, Muhamad Firdaus Syahmi; Mustafa, Shuhaimi; Mohd Hashim, Amalia; Yusof, Mohd Termizi; Zulkifly, Shahrizim; Malek, Ahmad Zuhairi Abdul; Roslan, Muhamad Akhmal Hakim; Mohd Asrore, Mohd Shaufi (Elsevier BV, 2023)
Bacillus velezensis FS26 is a bacterium from the genus Bacillus that has been proven as a potential probiotic in aquaculture with a good antagonistic effect on Aeromonas spp. and Vibrio spp. Whole-genome sequencing (WGS) allows a comprehensive and in-depth analysis at the molecular level, and it is becoming an increasingly significant technique in aquaculture research. Although numerous probiotic genomes have been sequenced and investigated recently, there are minimal data on in silico analysis of B. velezensis as a probiotic bacterium isolated from aquaculture sources. Thus, this study aims to analyse the general genome characteristics and probiotic markers from the B. velezensis FS26 genome with secondary metabolites predicted against aquaculture pathogens. The B. velezensis FS26 genome (GenBank Accession: JAOPEO000000000) assembly proved to be of high quality, with eight contigs containing 3,926,371 bp and an average G + C content of 46.5. According to antiSMASH analysis, five clusters of secondary metabolites from the B. velezensis FS26 genome showed 100 similarity. These clusters include Cluster 2 (bacilysin), Cluster 6 (bacillibactin), Cluster 7 (fengycin), Cluster 8 (bacillaene), and Cluster 9 (macrolactin H), which signify promising antibacterial, antifungal, and anticyanobacterial agents against pathogens in aquaculture. The probiotic markers of B. velezensis FS26 genome for adhesion capability in the hosts’ intestine, as well as the acid and bile salt-tolerant genes, were also detected through the Prokaryotic Genome Annotation System (Prokka) annotation pipeline. These results are in agreement with our previous in vitro data, suggesting that the in silico investigation facilitates establishing B. velezensis FS26 as a beneficial probiotic for use in aquaculture.